Caracterização microestrutural e propriedades mecânicas em pinos para transmissão mecânica de aço inoxidável martensítico e pinos fusíveis de latão em chave de alta tensão - Pereira, Luiz Eduardo Rodrigues [UNESP] (2015)
This work analyzed the microstructure and mechanical properties of mechanical transmission pins of the switchgear Magrini Gallileo, MSM series. The transmit pin is manufactured of stainless steel AISI 420 and heat-treated and fuse pin in brass ASTM C36000, commercially known as Brass Cut Free American. During operation of the switchegear, there may be disruptionof the fuse pin and its replacement becomes a priority leaving the blackground the ongoing conducted by the switchgear. These fuse pins are located in the upper region of the switchgear and installed therefore the key energized side. The exchange of the seitchgear takes a long time and a high risk maintenance. The goal is to change positions between mechanical transmission pins and the fuse pin, avoiding that the technician be exposed to energized side key during maintenance. The mechanical properties were studied by metallographic characterization by optical microscopy, S.E.M. (Scanning Electron Microscopy) and the pin mechanical properties were obtained by strain, shear and hardness test. The laboratory tests showed that the shear stress of brass ASTM C36000 fuse pin is 30% of the shear pin transmission AISI 420 stainless steel hardened by temper. With these results, the substitution can be made with good safety margin and the equipment operates correctly, reducing the time to switch power off and consequently the e-energized line